Percy Manning : the man who collected Oxfordshire - Heaney, Michael (Archaeological lives., 2017)
This volume provides the first detailed biography of Percy Manning (1870-1917), an Oxford antiquary who amassed enormous collections about the history of Oxford and Oxfordshire.